2010
DOI: 10.2478/v10101-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-linear periodisation training on the explosive force and plasma testosterone

Abstract: SummaryStudy aim: To evaluate the effects of two strength training programmes on the explosive force of lower extremities and total testosterone levels in plasma of Brazilian football players. Material and methods: A group of 24 male football players aged 16 -19 years participated in a 12-week training: non-linear periodised (NLP) or non-periodised (NP), 12 subjects each. Before and after training period, all subjects performed countermovement vertical jump (CMJ), horizontal jump and Flegner's power test, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The authors suggested that, due to the high level of training in athletes, a periodization of 12 weeks was not sufficient to cause an increase in muscle strength. Alternatively, Souza et al, (2010) observed that 12 weeks of linear and DUP resistance training induced significant changes for vertical and horizontal jump performances in young soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that, due to the high level of training in athletes, a periodization of 12 weeks was not sufficient to cause an increase in muscle strength. Alternatively, Souza et al, (2010) observed that 12 weeks of linear and DUP resistance training induced significant changes for vertical and horizontal jump performances in young soccer players.…”
Section: Discussionmentioning
confidence: 99%